An Enhanced Blue Light Emitting Diode (International Journal of Engineering and Computer Science, 2015)
This research produces a highly efficient energy saving electroluminescent enhanced blue light emitting diode.The fabrication of this enhanced blue LED involves the growth of a complex semiconductor crystal with advanced heterostructure bandgap design and absolute optimization of the light out-coupling to maximize efficiency.This research discusses innovative ideas which enhance the efficiency of the white light source by critically analyzing the processes involved. It covers the fabrication of blue GaN LED chip, channeled at improving the efficacy of each building block stage from Substrates, Buffers and Epitaxy, to Physics, Processing and Devices, to Lamps, Luminaires and Systems.